Pengaruh Level Formalin dan Frekuensi Penambahan Litter terhadap Karakteristik Litter Ayam Broiler (The Effect of Formalin Level and Litter Addition Frequency on the Characteristics Broiler Litter) - Nur Widodo; Wihandoyo (Wihandoyo); Supadmo (Supadmo) (Buletin Peternakan, 2009)
The research was conducted to evaluate the effect of formalin level and litter addition frequency on the broiler litter characteristics. One hundred and fifty broiler chickens were divided into 10 litter treatment with three replicationand five chickens each. The treatments were combination level of formalin sprayed (0, 4, 8, and 12%) and frequencies of spraying (every 1, 2, and 3 weeks) on to litter (D0F0, D4F1, D4F2, D4F3, D8F1, D8F2, D8F3, D12F1, D12F2 dan D12F3). The data collected were pH, temperature, total bacterial, and ammonia concentration in the litter of broiler chicken. The results showed that level of formalin sprayed (0, 4, 8 and 12%) and frequencies of sprayed (every 1, 2, and 3 weeks)on to litter had not significantly affected litter pH (8.3; 8.7; 8.8; 9.0; 9.0; 9.2; 9.0; 9.0; 9.8 and 9.0) litter ammonia contents (317.1; 475.2; 454.5; 425.3; 218.4; 300.1; 384.0; 375.3 and 417.2 ppm) for (D0F0, D4F1, D4F2, D4F3, D8F1, D8F2, D8F3, D12F1, D12F2 dan D12F3) respectively. Litter temperature had significant differences (33.89; 32.31; 32.83; 32.58; 32.81; 32.81; 32.42; 32.28; 33.28 and 32.72 0C) and total litter of bacteria (1.7X108;1.1X108; 9.9X107; 1.2X108; 7.1X107; 8.5X107; 1.1X108; 4.8X107; 4.8X107; 4.9X107 and 8.2X107 CFU). It is concluded that the formalin sprayed as much as 12% to litter every 1 week (D12F1), produced the best result to reduced littertotal bacteria, but had not decreated the ammonia litter.(Key words: Broiler chicken, Formalin, Litter, Total bacteria, Ammonia)